Clinical research from information systems practice. Issue 1 (2nd January 2023) - Baskerville, Richard; Vom Brocke, Jan; Mathiassen, Lars; Scheepers, Helana
ABSTRACT: An increasing presence of practitioners with doctoral degrees in Information Systems and related disciplines holds promise to advance Information Systems research. The prospect is to gain more knowledge from the practical experience of developing, using, and managing information systems in context. To scientifically capitalise on this opportunity, this EJIS special issue introduces the research genre of "Information Systems Clinical Research". The genre presents knowledge generated from practitioner-researcher interventions to achieve desired outcomes in information systems development, use, and management practice contexts. In this editorial, we introduce and conceptualise the genre; we present a research framework that defines its four key elements; and we discuss how to address its key challenges in research projects. As a result, we derive ten criteria for rigorous Information Systems Clinical Research and provide examples on how the articles published in the special issue have addressed these criteria. We conclude with a call to further advance clinical research as an important part of the Information Systems discipline.